Empathy as a crucial skill in disrupting disparities in global brain health - Fitri, Fasihah Irfani; Lage, Carmen; Mollayeva, Tatyana; Santamaria-Garcia, Hernando; Chan, Melissa; Cominetti, Marcia R.; Daria, Tselmen; Fallon, Gillian; Gately, Dominic; Gichu, Muthoni; Giménez, Sandra; Zuniga, Raquel Gutierrez; et al. (Frontiers in Neurology, 2023)
Brain health refers to the state of a person’s brain function across various domains, including cognitive, behavioral and motor functions. Healthy brains are associated with better individual health, increased creativity, and enhanced productivity. A person’s brain health is intricately connected to personal, social and environmental factors. Racial, ethnic, and social disparities affect brain health and on the global scale these disparities within and between regions present a hurdle to brain health. To overcome global disparities, greater collaboration between practitioners and healthcare providers and the people they serve is essential. This requires cultural humility driven by empathy. Empathy is a core prosocial value, a cognitive-emotional skill that helps us understand ourselves and others. This position paper aims to provide an overview of the vital roles of empathy, cooperation, and interdisciplinary partnerships. By consciously integrating this understanding in practice, leaders can better position themselves to address the diverse challenges faced by communities, promote inclusivity in policies and practices, and further more equitable solutions to the problem of global brain health.